Suicide Prevention: Current Status - Jiloha, RC (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2019)
According to the WHO, around 8 lakhs people die of suicide every year and up to 25 times as many make a suicide attempt. Attempted suicide is self-injury with the desire to end oneâ€™s life that does not culminate in death. According to the Section 309 of Indian Penal Code (IPC), suicide attempt was considered as an offence. It might have been implemented to act as a deterrent to prevent suicidal attempts. However, suicide attempts occur in the background of severe mental stress. According to a previous study, 93% of suicide attempters were found to be mentally unwell at the time of commission of suicide attempt. Therefore, it is necessary to decriminalize suicide. Universal attempt to decriminalize suicide has been made. In India, Sec 309 IPC has remained untouched and not amended for the past 155 years, thus warranting a relook and repeal. The Delhi High Court first condemned Sec 309 IPC as â€œanachronism unworthy of societyâ€ (1985). Supreme Court in 1994 called it â€œirrational and cruel and hence voidâ€ which was then overruled by a panel of judges.